Women's Role in Fish Processing for Business Sustainability at Depok Beach - Nur Auliatun Nissa Zulfa; Kumala Sari Ayu; Ajri Miftahul; Mada Zahra Varka; Nurmalasari Nevia; Restutami Herjiwandini Indah (SHS Web of Conferences)
This study explores the role of women in fish processing at Depok Beach, Bantul Regency, and its impact on the long-term sustainability of local fishing businesses. The aim is to assess how women's involvement influences business survival and growth in the fishing sector. The research, conducted between May and June 2024, involved 72 women engaged in fish processing, using observation, interviews, and documentation techniques for data collection. The results indicate that women's participation significantly supports the local economy by maintaining traditional fish processing methods that meet market standards, promoting resource and waste management, and enhancing community participation. However, challenges such as financial limitations and lack of technological access limit their ability to innovate and expand. These gaps highlight the need for policy changes and increased support for women in the sector. The study concludes that empowering women is essential for the sustainability of fish processing businesses in Bantul Regency, and recommends investing in capacity-building programs to overcome barriers and maximize their potential. The findings provide actionable insights for policymakers and stakeholders to foster sustainable coastal development.